Effects of the ice popsicle on vasopressin, osmolality, thirst intensity, and thirst discomfort - Thammy Gonçalves Nakaya; Marilia Ferrari Conchon; Aline Korki Arrabal Garcia; Ernane Torres Uchôa; Lígia Fahl Fonseca (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To analyze the effects of the ice popsicle on vasopressin, osmolality, thirst intensity, and thirst discomfort. Method: This is a quasi-experimental, pre- and post-test study conducted in a laboratory. The sample consisted of nine healthy male volunteers, who received 2% hypertonic saline solution. Results: Popsicle intake did not result in a statistically significant reduction in vasopressin levels (F=0.876 and p=0.428). However, there was a reduction in the hormonal physiological profile of vasopressin from 7.1 pg/ml to 5.8 pg/ml after the first two interventions. Osmolality concentration changed from 270.65 to 286.51 mOsm/kg, with no statistical difference (F=2.207; p=0.09). Ice popsicles significantly reduced thirst intensity (F=10.00; p=0.001) and thirst discomfort (F=10.528; p <0.001). Conclusion: There was a reduction in thirst intensity and discomfort after the use of the 20 ml ice popsicle. There was no statistical difference for vasopressin and osmolality. However, there was a reduction in the hormonal physiological profile of vasopressin during 30 minutes of intervention.